If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1.2 = 3.9 Reorder the terms: 1.2 + 3x = 3.9 Solving 1.2 + 3x = 3.9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.2' to each side of the equation. 1.2 + -1.2 + 3x = 3.9 + -1.2 Combine like terms: 1.2 + -1.2 = 0.0 0.0 + 3x = 3.9 + -1.2 3x = 3.9 + -1.2 Combine like terms: 3.9 + -1.2 = 2.7 3x = 2.7 Divide each side by '3'. x = 0.9 Simplifying x = 0.9
| (-2)-(-6)-4= | | 4v+7=2v+15 | | 5x+5=(x-1) | | 2+2=7-3 | | 4-(8+2n)=-2(n+2) | | 9x^2-79x+56=0 | | -8x+24=0 | | 25x+5x-15=0 | | 9x-11=4x+6+5x+5 | | 9(m+2)+1=19+9m | | 5t+10=2t+31 | | 2x+4y+7=0 | | 21+2w=p | | 2x-2x+2=0 | | -2-3y=22 | | 5x=21+2a | | -x+4x=0 | | 3v+10=31 | | 4g+9=2g+17 | | Y=(-x)+8 | | -4x-2x-6=0 | | 2x+4=100000 | | 443x+8=11 | | Y=-12x | | -7x+9x+4=0 | | 6+4(3-k)=2(-2k+9) | | 12=3v-15 | | 8p-8=10-3p | | 5-2y=y | | 4x^2-9x+11=2x+5 | | 8x^3+24x-24x^2-8=0 | | 4x^2+24x+8=0 |